Respuestas

  • Usuario de Brainly
2013-06-11T05:08:56+02:00
                                          x=1
f(1)= - 2(1)+1  →  f(1)= - 1  
g(1)=1² -1   →  
g(1)=0
h(1)=√(1+3) →
h(1) = 2

                                        
x=6
f(x)= - 2.6+1→ f(6)= - 12+1   → f(6)= - 11  
g(x)=6² -1  →g(x) = 35
h(x)=√(6+3) → h(x) = 3
                                             x=a-3
f(a -3)= - 2(a -3)+1              g(1)=(a-3)² -1                              h(1)=√((a-3)+ 3)
f(a -3)= - 2a + 7                  g(a -3)=a² - 6a + 8                       h(a -3)=√(a)

                                           x=√a
f(√a)= - 2(√a)+1              g(√a)=(√a)² -1                              h(√a)=(√(√a)+ 3)
f(√a)= - 2√a+1                 g(√a)=a -1                                   h(√a)=4^√a+ 3

                                          x=0

F(0) = (0+1)/(0-2)                                  G(x)= 2^(-0) - 1- √(-0)
F(0) = -1/2                                            G(x)= 0

                               x= - 1
F(x) = (- 1+1)/(- 1-2)                              G(x)= 2^(-(-1)) - 1- √(-(-1))
F(x) = 0/ - 3                                          G(x)= 2^1 - 1- √1
F(x) = 0                                                G(x)= 0

                                       x=-4

F(x) = (-4+1)/(-4-2)                                G(x)= 2^(-(-4)) - 1- √(-(-4))
F(x) = -3 / - 6                                       G(x)= 2^4 - 1- √4
F(x) = 1/2                                           G(x)= 13

                         X = - a²

F(x) = -a²+1/-a² - 2                                          G(x)= 2^ a² - 1- √a²
F(x) = a²-1/a² + 2                                             G(x)= 2^ a² - 1- a

espero que te sirva, salu2!!!!